O Trabalho pedagógico do professor e suas implicações no processo de apropriação da língua materna escrita - Marchetti, Tatiana (2018)
This dissertation was presented to the Stricto Sensu Postgraduate Program in Education, master's level, from the State University of the West of Paraná - UNIOESTE, in the line of research Teacher Training and Teaching and Learning Processes. The author is a member of the Research Group on Education and Teacher Training - GPEFOR, from the same university. The object of this research is the teacher’s pedagogical work and its implications in the process of written native language acquisition. The main question of the research was: how is pedagogical work done in the classroom, in the process of acquisition of the written native language and what are the implications of this process? The general objective of the research was to understand how is the pedagogical work done in the classroom and the implications of this work on the teaching process of the written native language. As specifics objectives have been delimited: to investigate the accomplishment of the teacher’s pedagogical work with a view to the acquisition of the native language written by the student ; identify how the teaching actions interfere in the learning of the written native language; and to understand the challenges that are established for an effective and consequent teaching practice in the teaching of written native language. The research was carried out through bibliographical and field research. It was constituted of primary sources, through interviews guided by semi-structured scripts that were later transcribed; observation of the pedagogical work of the teacher; and teacher/student interaction in the classroom, recorded in a field diary. Three teachers who work in classes of the 3rd year of Elementary School of the public-school network of the city of Cascavel-Pr constitute the subjects interviewed. The questions addressed to the subjects of the research provided access to information about how the organization is run and the direction of teacher’s work in the moments of the productions written by the student. The bibliographical research was carried out through reading, writing and analysis of works by classical authors such as BAKHTIN (2003, 2004), VIGOTSKY (2005, 2014) and LEONTIEV (1978, 2014), which contribute to the language and human development. The analysis of the data obtained during the research was based on the Bakhtin language perspective, from the categories: dialogism, mediation, and activity. We verified that, for the implications of the teacher's work to take place favorably for the effective teaching of written mother tongue it is important to understand how the student learns, how the teacher teaches and how to present the object to be taught, based on a theoretical conception that considers the process of teaching and learning as a process of interaction and space of meanings movement